Evaluation of Forage Grasses Yield and Nitrogen Use Efficiency in Response to Combined Application of Spent Mushroom Substrate and Mineral Nitrogen - Beata Wiśniewska-Kadżajan; Elżbieta Malinowska (Agronomy)
In the era of the intensive use of mineral fertilizers, which results in a negative impact on the natural environment, it is necessary to use agrotechnical practices that use the potential of biodegradable waste. The physicochemical properties of the substrate after mushroom cultivation (SMS—spent mushroom substrate) mean that this waste can be a safe and cheap source of ingredients for crops. The aim of this study was to investigate the effect of different doses of mineral fertilizers and SMS on the yield of two grass species, the nitrogen content in their biomass, and its uptake and use efficiency, as well as its accumulation in the soil. This research was based on a three-year (2017–2019) experiment that was conducted in bottomless pots in field conditions at the experimental facility of the University of Siedlce, Poland. The SMS was used together with mineral fertilization in various proportions. Two forage grass species were tested: Dactylis glomerata and Phleum pratense. In each year, three harvests of the cultivated grasses were collected. The introduction into the soil of the medium dose of the SMS nitrogen, supplemented annually with the medium dose of mineral nitrogen (SMS2 + N2PK), resulted in the greatest yield of the grasses (19.98 g·pot−1), as well as its greatest uptake (410.2 g·pot−1) and use efficiency (105%). The highest content of nitrogen (21.60 g·kg−1) was in the plants treated with the smallest dose of the SMS and supplemented with the greatest dose of the mineral nitrogen (SMS1 + N3PK). The greatest dose of the SMS nitrogen, applied with the smallest amount of the mineral nitrogen (SMS3 + N1PK), resulted in the most (1.70 g·kg−1) nitrogen accumulation in the soil.